Electromagnetic pollution in the urban environment and risk or cancer - Burgos-Molina, Antonio Manuel; Ruiz-González, O.M.; Ledesma-Tomé, F.A.; Soto-Pinilla, J.; Sánchez-Jiménez, M.; González-Vidal, A.; Ruiz-Gómez, Miguel José (ASEICA, 2024)
Social, national and international interest in the health risks of exposure to electromagnetic fields in the urban environment is growing in our increasingly technological Society. In Spain, very few measurements have been made in cities, while in other countries such as Canada, exposure levels have been evaluated in more than 60 cities. The International Agency for Research on Cancer (IARC) has classified low-frequency magnetic fields as “possibly carcinogenic” in humans. It is important that Information Systems include data about urban exposure levels and their relationship with cancer incidence in order to minimize risks. To date, it is still not clear what is the molecular mechanism of interaction between magnetic field and biological tissue. There is evidence that magnetic fields could increase the production of reactive oxygen species, induce damage to the DNA molecule and alter signaling pathways that lead to carcinogenesis; although it is still not sufficiently demonstrated.
Keywords: Inmunidad; Cáncer; Immune system